2011
DOI: 10.1093/aje/kwr206
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Shingles Incidence and Complication Rates From Medical Record Review and Administrative Database Estimates: How Close Are They?

Abstract: Accurate rates of herpes zoster incidence and complication have become of greater interest as studies have suggested an increasing temporal trend in incidence rates across all age groups and long-term follow-up studies of vaccine effectiveness are required by the Food and Drug Administration. This study compares the results obtained from the most commonly used method to obtain herpes zoster data (rates obtained from administrative data) with results obtained when administrative data are supplemented by medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 42 publications
3
68
1
Order By: Relevance
“…However, administrative database studies using diagnostic and billing codes may have overestimated the incidence due to misclassification. Several validation studies reported a relatively high sensitivity for the International Classification of Diseases (ICD)-9 code (98%) and positive predictive value (PPV; 84–94%) 15 83 139. Furthermore, studies using administrative insurance data may lack generalisability because they may not be representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, administrative database studies using diagnostic and billing codes may have overestimated the incidence due to misclassification. Several validation studies reported a relatively high sensitivity for the International Classification of Diseases (ICD)-9 code (98%) and positive predictive value (PPV; 84–94%) 15 83 139. Furthermore, studies using administrative insurance data may lack generalisability because they may not be representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Medical record reviews were not performed to confirm the diagnosis of herpes zoster because a study validating herpes zoster diagnosis codes reported confirmation in slightly more than 85% of the cases. 25 Patients with an outcome diagnosis recorded in the 6 months before vaccination were not counted as a new-onset outcome in the 42-day risk window. The occurrence of disseminated VZV was captured from emergency department visits and hospitalizations, and herpes zoster events were captured from outpatient clinic visits, emergency department visits, and hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, evidence that herpes zoster diagnoses are confirmed on medical record review in a high percentage of cases. 25 Note that the baseline disease conditions were also based on diagnosis codes without medical record confirmation. Second, the small number of herpes zoster cases in the risk window for current users precluded an analysis of individual immunosuppressant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Both studies used electronic-billing data without medical record confirmation which can result in misclassification of both exposure (vaccination status) and outcome (occurrence of HZ). 1,17 Furthermore, neither provided clinical information on HZ characteristics among vaccinated persons, precluding a complete description of the vaccine's impact. We evaluate HZ vaccine performance in a community setting using medical record review to confirm HZ vaccination and case status and compare the characteristics of HZ by vaccination status.…”
Section: Introductionmentioning
confidence: 99%